2009
DOI: 10.1586/erv.09.77
|View full text |Cite
|
Sign up to set email alerts
|

DNA vaccines in veterinary use

Abstract: DNA vaccines represent a new frontier in vaccine technology. One important application of this technology is in the veterinary arena. DNA vaccines have already gained a foothold in certain fields of veterinary medicine. However, several important questions must be addressed when developing DNA vaccines for animals, including whether or not the vaccine is efficacious and cost effective compared with currently available options. Another important question to consider is how to apply this developing technology in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 108 publications
(66 reference statements)
0
64
0
Order By: Relevance
“…The vaccines have been advanced to be applied in the management of other complicated medical conditions in genetics such as neurological disorders and cancer (Shimamura et al, 2011;Alam and McNeel, 2010). The technology of gene modification has also been employed in the veterinary field to help the control of the West Nile virus, hematopoietic necrosis virus and melanoma in horses, salmon and dogs, respectively (Redding and Weiner, 2009). Among the applications in humans, the licensing of DNA vaccines is limited because of the possible implications that have not been thoroughly investigated and approved.…”
Section: Overview Of Gene Vaccinationmentioning
confidence: 99%
“…The vaccines have been advanced to be applied in the management of other complicated medical conditions in genetics such as neurological disorders and cancer (Shimamura et al, 2011;Alam and McNeel, 2010). The technology of gene modification has also been employed in the veterinary field to help the control of the West Nile virus, hematopoietic necrosis virus and melanoma in horses, salmon and dogs, respectively (Redding and Weiner, 2009). Among the applications in humans, the licensing of DNA vaccines is limited because of the possible implications that have not been thoroughly investigated and approved.…”
Section: Overview Of Gene Vaccinationmentioning
confidence: 99%
“…It is the first marketable DNA vaccine and its prices are comparable to other existing vaccines against WNV. 31 The DNA vaccines available in the market today are summarized in Table II. It can be taken as a first step towards DNA vaccination in human beings just like first vaccine against smallpox was started by taking antigen samples from the cow.…”
Section: In the Marketmentioning
confidence: 99%
“…The demand for plasmid DNA (pDNA) for vaccine and gene therapy applications has increased during the past few years in response to several technical improvements and the recent licensing of four DNA products for veterinary applications (Redding and Weiner, 2009). A detailed review on the current progress in this field can be found elsewhere (Kutzler and Weiner, 2008;Redding and Weiner, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A detailed review on the current progress in this field can be found elsewhere (Kutzler and Weiner, 2008;Redding and Weiner, 2009). pDNA, used for gene delivery, has attracted a lot of interest since it offers several advantages over viral gene delivery, e.g.…”
Section: Introductionmentioning
confidence: 99%